Concepções e práticas de educação ambiental: uma análise a partir das matrizes teóricas e epistemológicas presentes em escolas estaduais de ensino fundamental de Santa Maria-RS - Kist, Anna Christine Ferreira (2010)
The environmental education (EE) presents different conceptions which reflect distinct projects of the society; on one hand, a critical, emancipating, and free conception based on the dialogical and liberating from Paulo Freire (1996); on the other hand, according to Bruguer (2004), a taming conception, once it only teaches how to take care of the environment. The absence of a critical, historical, political and social analysis of the environmental matter is a factor that has some influence in this context. This fragmentation contributes a lot in the different ways on how teachers understand and produce the EE. In this dissertation, the EE is understood as a tool of social transformation in the searching of better, fairer world, which has life quality and social and environmental justice. The main purpose of this research was to identify and to discuss the theoretical and epistemological matrixes associated to the teaching practices on EE, developed in the state schools of complete fundamental schooling, located in the urban area of Santa Maria, RS state. In order to develop this paper, a sample of five state schools was taken and, as subjects, five representatives of the 8th Educational Coordination, schools managers (direction or vice-direction, coordination) and teachers of fundamental schools. The study used a qualitative methodology, trying to discuss the practices of EE carried out in schools from the analysis of contents of the documents produced and from the analysis of the speeches of the involved subjects. The result analysis allowed to conclude that the predominant matrix, which is orientating the practices on EE, is the traditional one, once: the teachers seem not to understand and to apply the transversal action proposed in EE; it is noticed that there is no presence of the National Politics for the Environmental education in the classroom; managers and teachers translate, in their speeches, an understanding of EE strictly linked to the practices of conservation of the natural resources; the Pedagogical Political Projects (PPP) of schools did not indicate the suitable time and space for the development of perceptions and integrating actions to transform the social and environmental reality of students. Thus, it is recommended: (i) a greater availability of time and material resources for the managers of EE in the 8th Educational Coordination; (ii) commitment and formation for the school managers and teachers; (iii) a PPP that has clear orientations for the integrating EE practices; (iv) suitable conditions for the teachers.